Photocatalytic degradation of gas pollutants on self-assembled titania nanotubes - A. G. Kontos; Katsanaki, A.; Maggos, T.; V. Likodimos; Ghicov, A.; Kim, D.; Kunze, J.; Vasilakos, C.; Schmuki, P.; P. Falaras (Chemical Physics Letters, 2010)
Self-assembled titanium oxide nanotubular (NTs) arrays with vertical arrangement, tailored morphological properties and variable thickness were prepared by electrochemical anodization in ethylene glycol containing electrolytes. The NTs present significant UV photocatalysis against toluene and benzene at ppb concentrations, under normal conditions of temperature and pressure. The photocatalytic activity depends on the length of the NT arrays, showing a tendency of saturation for thickness above 2.5 μm and maximum efficiency for samples with thickness of 12 μm. The optimum NT structures outperform over standard Degussa P25 films rendering them very promising for outdoor photocatalytic applications. © 2010 Elsevier B.V. All rights reserved.